Penerapan Keterwakilan Perempuan Sebagai Pengawas Pemilu di Badan Pengawas Pemilu dalam UU Pemilu di Indonesia - Muharam, Ricky Santoso; Pradhanawati, Ari; Fitriyah; Supratiwi (Jurnal Bina Praja, 2023)
This study analyses the application of women's representation as election supervisors and election supervisors who are part of election organizers other than the General Elections Commission. The Election Supervisory Board (Bawaslu) is an election organizer with the authority and responsibility to oversee the process of election stages and election participants. This study uses a qualitative approach by using secondary data from the Bawaslu Decree of the Republic of Indonesia and primary data from the regulation of Law No. 7 of 2017 concerning general elections, journals, internet and social media from Bawaslu agencies, both from Bawaslu RI, Province, and Bawaslu Regency/City. Then, conclude using descriptive analysis techniques. The results of this study show that the implementation of women's representation in the election supervisory institution, namely Bawaslu, does not meet the women's representation requirement of 30%. Even in some districts/cities, women are not represented as election supervisors. Article 92 Paragraph 11, as a legal basis regarding women's representation in Bawaslu, is not fully implemented. Regulations are not only used as an obligation abort as a condition for women's entry into politics that have been given places and rules. In addition, implementation and supervision in the field are needed. There needs to be integrity and transparency from the selected selection team with no political content that benefits one candidate. However, due diligence and appropriateness are in the realm of Bawaslu of the Republic of Indonesia.